Does Accreditation Status Affect Job Performance of the Electronic Medical Record Clerks at Community Health Center? - Harinto Nur Seha; Didik Tamtomo; Endang Sutisna Sulaeman (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: Primary care doctors and other staff working in primary care require comprehensive and accurate data on patients at the point-of-care if they are to provide high quality health services to their patients. Electronic patient records are an effective method of achieving this objective, by dispensing with the need to use difficult to access, and often illegible, paper-based records. This study aimed to analyze the effect of accreditation status on job performance of the electronic medical record clerks at community health center.Subjects and Method: This was an analytic observational study with a cross-sectional design. The study conducted for 25 puskesmas (community health centers), in Yogyakarta, from March to June 2018. A sample of 200 patient medical records was selected by simple random sampling. The dependent variables were completeness and accuracy of medical record. The independent variables were tenure and multi task as level 1 in the multilevel model (MLM). Accreditation status of puskesmas was taken as level 2 in the MLM. The data were collected by questionnaire and analyzed by MLM.Result: Longer tenure (b= 1.03; 95% CI= 0.30 to 1.77; p= 0.006) and single task occupation (b= 4.21; 95% CI= 6.23 to 2.20; p<0.001) were positively associated with completeness of electronic medical record. Likewise, longer tenure (b= 0.54; 95% CI= 0.079 to 1.01; p= 0.022) and single task occupation (b= 2.14; 95% CI= 3.42 to 0.87; p= 0.001) were positively associated with accuracy of medical record medical record. Accreditation status of puskesmas showed negligible contextual effect on completeness (ICC= 0.36%) and accuracy (ICC= 1.17%) of the electronic medical record.Conclusion: Longer tenure and single task occupation are positively associated with completeness and accuracy of medical record. Accreditation status of puskesmas shows negligible contextual effect on completeness and accuracy of the electronic medical record.Keywords: completeness, accuracy, tenure, occupation, accreditation status, community health center, electronic medical recordCorrespondence: